2012
DOI: 10.1186/1472-6823-12-22
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, insulin and thyroid hormones in a cohort of Egyptian obese Down syndrome children: a comparative study

Abstract: BackgroundObesity is a major worldwide health problem. It is commonly observed in Down syndrome individuals than in the general population. The reason for increased risk of obesity in DS is unclear.The current study was designed to clarify differences in some obesity- related hormones in a group of prepubertal Down syndrome children.MethodsThirty six Egyptian children with Down syndrome were enrolled in this study, divided according to their body mass index (BMI) into 23 obese and13 non obese. Another group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…39 As expected, these comorbidities also are frequent in overweight/obese children with DS. 14,18,19 Congenital heart diseases are the main causes of death among young with DS (<20 years old). 40 However, children and adults with DS also experienced excess mortality as the result of other causes, such as cancers, infections, type 2 diabetes, and liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 As expected, these comorbidities also are frequent in overweight/obese children with DS. 14,18,19 Congenital heart diseases are the main causes of death among young with DS (<20 years old). 40 However, children and adults with DS also experienced excess mortality as the result of other causes, such as cancers, infections, type 2 diabetes, and liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies reported that high levels of leptin, a well-known adipocytokine, could be an additional determinant of obesity in children with DS. [13][14][15] Similarly to children without DS, obesity in children with DS is associated with several diseases including obstructive sleep apnea, 16 orthopedic and gait abnormalities, 17 and metabolic syndrome features such as dyslipidemia and hyperinsulinemia. 14,18,19 Epidemiologic studies found together with the increase in pediatric obesity, an increased prevalence of nonalcoholic fatty liver disease (NAFLD).…”
mentioning
confidence: 99%
“…At the same time, we are also seeing greater problems with lifestyle‐related diseases in the general population. Although the exact prevalence of these lifestyle‐related diseases in patients with Down's syndrome remains uncertain, a number of previous studies have examined dyslipidaemia, insulin resistance and hyperuricaemia, especially in late adolescence or adulthood . Obesity plays a key role in the occurrence of these morbidities in individuals with intellectual disabilities, including Down's syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Down's syndrome experience a number of complications, including cardiac malformation, hypothyroidism, hearing impairment, ophthalmic problems and coeliac disease, and they are also more susceptible to leukaemia . In addition, a variety of metabolic disorders have been observed in Down's syndrome, such as dyslipidaemia , insulin resistance and hyperuricaemia, abnormally high levels of uric acid in the blood . Although the exact cause of these metabolic disorders remains unclear, obesity is thought to play an important role, especially if it starts in late adolescence .…”
Section: Introductionmentioning
confidence: 99%
“…An increase in CK serum levels is not a typical feature of DS, although a significant increase in CK values is reported in obese DS patients compared with nonobese ones. [9] Our patient, who had both high serum CK levels and a myopathic electromyography pattern, underwent skeletal muscular biopsy, which revealed a weak Dys 3 immunostain compatible with a diagnosis of BMD. The diagnosis was confirmed by DMD gene analysis, which revealed an intronic splice-site mutation causing exon 15 skipping and keeping the reading frame intact.…”
Section: Discussionmentioning
confidence: 99%